2017
DOI: 10.18632/oncotarget.16121
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic features of neuromedin U in breast cancer are associated with NMUR2 expression involving crosstalk with members of the WNT signaling pathway

Abstract: Neuromedin U (NMU) has been shown driving the progression of various tumor entities, including breast cancer. However, the expression pattern of NMU and its receptors in breast cancer tissues as well as systematic insight into mechanisms and downstream targets of the NMU-driven signaling pathways are still elusive. Here, NMU expression was found up-regulated in all breast cancer subtypes when compared to healthy breast tissue. Using an in silico dataset comprising 1,195 samples, high NMU expression was identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 55 publications
4
11
0
Order By: Relevance
“…Although no experimental data has suggested a direct link between NMU and thyroid cancer, NMU has been shown to promote the development of various tumors, including breast cancer. Garczyk S et al have demonstrated that NMU may contribute to the progression of NMUR2-positive breast cancer [21] and enhance resistance to tumor immune responses in breast cancers with HER2 overexpression [22], suggesting NMU is a potential drug target for personalized strategies. Furthermore, NMU is involved in the development of endometrial, colorectal and gastric cancers, as well as acute myeloid leukemia caused by TP53 mutations [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Although no experimental data has suggested a direct link between NMU and thyroid cancer, NMU has been shown to promote the development of various tumors, including breast cancer. Garczyk S et al have demonstrated that NMU may contribute to the progression of NMUR2-positive breast cancer [21] and enhance resistance to tumor immune responses in breast cancers with HER2 overexpression [22], suggesting NMU is a potential drug target for personalized strategies. Furthermore, NMU is involved in the development of endometrial, colorectal and gastric cancers, as well as acute myeloid leukemia caused by TP53 mutations [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that overexpression of NMU is associated with tumorigenesis and development of various malignancies [12][13][14][15][16][17][18][19]. However, to date no studies have examined the association of NMU and HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The neuropeptide has been demonstrated to be associated with a range of different physiological functions, including smooth muscle contraction, energy homeostasis, nociception, circadian control, bone remodeling, and immune regulation [9][10][11]. A limited number of studies had suggested that NMU may play an oncogenic role in the progression of various cancers, including lung cancer, pancreatic cancer, breast cancer, renal cancer, and endometrioid endometrial carcinoma, through promoting migration, invasion, glycolysis, a mesenchymal phenotype, a stem cell phenotype of cancer cells, and resistance to the anti-tumor immune response [12][13][14][15][16][17][18][19]. However, besides a report of NMU exacerbating non-alcoholic steatohepatitis (NASH) [20], the effects of NMU on liver diseases, especially on HCC, have not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The A260 nm/A280 nm ratio was generally between 1.9 and 2.0. Subsequently, cDNA was synthesized using 1μg of total RNA and the reverse transcription system (Promega) as described previously [ 32 ]. After cDNA synthesis, enzyme was heat inactivated by incubation for 5min at 95°C.…”
Section: Methodsmentioning
confidence: 99%
“…cDNAs were amplified by semi-quantitative real-time PCR using SYBR Green PCR mix (Bio-Rad Laboratories) and the iCycler IQ5 (Bio-Rad Laboratories) as described previously [ 32 ]. Gene-specific oligonucleotides were designed using Primer3web software (version 4.0.0) ( http://primer3.ut.ee/ ).…”
Section: Methodsmentioning
confidence: 99%